Factors Influencing the Adoption of Digital Banking: Generation Z in Surabaya - Kurniawan, Abraham Ivan; Morgan Gemiartha, Celine; Edbert Sudarsono, Jethson; Wijaya, Joshua; Adeline Yusuf, Keona; Linawati, Nanik (Journal of Accounting and Finance Management, 2025)
The study titled "Factors Influencing the Adoption of Digital Banking: Generation Z in Surabaya" examines the influence of digital financial literacy comprising financial knowledge, financial behavior, and financial attitude on the interest in adopting digital banking services among Generation Z in Surabaya. A quantitative research method was employed using a survey approach. The respondents consisted of 115 individuals aged 18–28 years in Surabaya, selected through purposive sampling. Data were collected via online questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS. The results indicate that financial behavior and financial attitude significantly influence the interest in using digital banking, while financial knowledge shows no significant effect. These findings offer valuable insights for digital banking service providers to tailor strategies that align with the financial behavior and preferences of young users.